The influence of the problem based learning model on students' mathematical problem solving ability in mathematical induction material - Syara, Lili; Habibah Pasaribu , Laili; Harahap, Amin (ARKA INSTITUTE, 2024)
The problem of low problem solving abilities of students in Mathematics subjects are due to the learning process in the classroom only directed at students' ability to memorize information, more lots of listening and writing, memorizing formulas and working on problems with formulas that have been memorized so that students have difficulty solving problems when finding differences from the example questions. This research aims to determine the use of the Problem Based Learning learning model and the problem solving abilities of class XI students at Muhamadiyah 10 Rantauprapat Private High School. This research is a type of quantitative research, with a research population of 120 students from 4 classes. Data collection techniques in this research used two methods, namely observation of teacher activities and tests in the form of descriptions. With research results tcount is greater than ttable. So it can be concluded that the Problem Based Learning (PBL) learning model has a very significant influence on the mathematical problem solving abilities of students in class This is strengthened because the Problem Based Learning (PBL) model has advantages and goals that are able to encourage students to learn more effectively because they focus on problem solving and students are able to develop themselves.